TINJAUAN KERAGAAN TANAMAN AREN (Arrenga pinnata Merr) DI KABUPATEN KUTAI BARAT - Abdul Fatah, dan Hery Sutejo (Universitas 17 Agustus 1945 Samarinda, 2015)
Self-sufficiency, which until now still not able to be met is considered very risky when looking at the situation the availability and level of world sugar prices are fluctuating. The emergence of the sugar import dependency is very risky for the survival of the national sugar industry. Self-sufficiency in addition to be pursued through the development of sugar cane as raw material also be expanded through other sources of raw materials as one of them is from the sugar plant.The study was conducted for about five months in West Kutai Regency (Sub Districts of Mook Manoor Bulatn and Damai). This study is a combination of literature review by direct observation in the field. Performance management sugar palm commodity will be traced through farmers practiced factual data on aspects of the production system, namely technical culture and to some extent on the aspects of post-harvest. The performance and then evaluated from the perspective of existing degraded land use in the study area.In Kutai Barat, broad palm plants reached 278.45 ha with a production of 35.81 tons in the form of palm sugar. This palm plant spread and the body naturally in many districts that have the lowlands to high topography. However, development centers and industrial plants are the most prominent palm sugar in Sub District of Mook Manaar Bulatn and Damai.The area of potential as development of the sugar plant one of which is the area that is in critical status by category or degraded, partly as a result of forest fires and land, encroachment, illegal logging, and farming are not environmentally friendly. Total land degraded in Kutai Barat (very critical to the critical potential) reaches ± 1,223,182.10 ha, which is in the forest area of ± 965 736 ha and is located outside the forest area of ± 305 974 ha.Cultivation of sugar, which is the source of raw material for making palm sugar, in the study area most derived from natural plants. Thus, the process of production systems (nurseries and land preparation, planting, and maintenance) are still many patterned on activities that are not in need of funds.Some of the problems found in farm management palm plants in the study area, among others, the production system is still not support the increased growth and development of the sugar plant, so the potential for water production sap into raw materials palm sugar is still not optimal. For post-harvest aspects, farmers are still faced with weak pricing position by the middlemen.